The stability of bifurcating steady states for a spatially heterogeneous cooperative system with cross-diffusion - Qian Xu; Guangping Chang (Advances in Difference Equations, 2018)
Abstract This paper investigates the stability of bifurcating steady states of a spatially heterogeneous cooperative system with cross-diffusion. According to the spectral analysis and the principle of exchange of stability, we show that the bifurcating steady states are stable.